Diet and gastric cancer - Šipetić Sandra B.; Tomić-Kundaković Slađana; Vlajinac Hristina D.; Janković Slavenka M.; Marinković Jelena M.; Maksimović Jadranka M. (Vojnosanitetski Pregled)
The aim of this case-control study, conducted in Serbia during the period 1998-2000, was to investigate whether diet was associated with the development of gastric cancer. The case group consisted of 131 patients with histologically confirmed gastric cancer, and the control group of 131 patients with orthopedics diseases and injuries. Cases and controls were individually matched by age (±± 2 years), gender, and place of residence. On the basis of multivariate logistic regression analysis, following factors were found as independent risk factors for gastric cancer: more frequent consumption of high-fat milk [Odds ratio (OR) =1.45, 95% confidence interval (CI) = 0.99-2.16]; mutton, lamb and/or calf meat (OR = 2.46, 95% CI = 1.11-5.47), sugar (OR = 2.13, 95% CI = 1.43-3.18), semi-white bread (OR = 2.09, 95% CI = 1.25-3.50), and salting food (OR = 5.72, 95% CI = 2.63-12.42). Factors found as protective were: more frequent consumption of margarine (OR = 0.41, 95% CI = 0.25-0.69), „other“ cheeses (OR = 0.47, 95% CI = 0.29 - 0.77), and fish (OR = 0.39, 95% CI = 0.19-0.76).